Four-Tier Diagnostic Test Untuk Mengidentifikasi Konsepsi Mahasiswa Sains Pada Program Merdeka Belajar Kampus Merdeka - Wicaksono, Ardian Trio; Mukarramah, Anisah (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2024)
The transformation of IAIN to UIN has had an impact on the addition of scientific disciplines, science. Science students are expected to have the ability to integrate basic Islamic knowledge and general science through introductory science integration courses in the MBKM curriculum. Initial interviews with science students revealed that they had difficulty integrating science and basic Islamic knowledge, so they needed an instrument to identify their conceptual profile. Four-tier diagnostic test is an instrument that can be used to identify conception profiles. The aim of the research is to determine the validity of the development of the Four-Tier Diagnostic Test and the Conceptual Profile of Science Students in the Introduction to Science Integration Course in Supporting the MBKM Program. The research subjects are science students who have taken introductory science integration courses. The instrument is in a four-tier test format with a 4D development model. Data collection techniques use questionnaires and tests which will be processed with descriptive analysis. Research results: (1) Validity of the development of 4 very valid criteria and 2 valid criteria, and (2) Science Student Conceptions Profile: understand the concept 20% do not understand the concept 42.58%; misconceptions 37.42%.